2019
DOI: 10.7759/cureus.6305
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Curriculum: A Good Thing?

Abstract: Introduction The hidden curriculum is defined as a set of influences that function at the level of the organizational structure and culture to impact learning. Literature supports the significant impact of the hidden curriculum on all levels of learners in medical education. Our project aims to capture the messages being delivered to healthcare providers at our local facility. Methods Multiple one-time educational sessions on the hidden curriculum were provided over a fiveyear period to healthcare professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…By undermining humanistic values, the hidden curriculum teaches students to prioritize "cure" over "care". It can also create a "cognitive dissonance with trainees' developed expectations distilled from the formal curricula" (Mackin et al 2019). Martimianakis et al (2015, S9) found that continued prevalence of the biomedical approach is related to the "denigration of 'nonscientific topics, such as medical history and the socio-cultural contexts of medicine.'"…”
Section: Medical School Curriculamentioning
confidence: 99%
See 4 more Smart Citations
“…By undermining humanistic values, the hidden curriculum teaches students to prioritize "cure" over "care". It can also create a "cognitive dissonance with trainees' developed expectations distilled from the formal curricula" (Mackin et al 2019). Martimianakis et al (2015, S9) found that continued prevalence of the biomedical approach is related to the "denigration of 'nonscientific topics, such as medical history and the socio-cultural contexts of medicine.'"…”
Section: Medical School Curriculamentioning
confidence: 99%
“…Because it is informal and culture-based, different interpretations exist on what exactly is the hidden curriculum; it is nuanced, and varies by institution, specialty or subspecialty, and of course by the individual physicians who impart it to students. Additionally, literature on the subject identifies many aspects of medical training as shaped by the hidden curriculum, including power-hierarchy issues in training and patient care, attitudes towards different specialties, patient dehumanization, emotional suppression, and burnout or work-life balance (Gaufberg et al 2010 ; Hopkins et al 2016 ; Mahood 2011 ; Mackin et al 2019 ; Rajput et al 2017 ) in essence influencing moral values and virtues of physicians rather than the primary informational content or therapeutic models of medical education. Most important in this context is that the hidden curriculum has a direct influence on students’ development with regard to their orientation towards patient-centered care (Bandini et al 2017 ; Haidet et al 2005 ).…”
Section: Medical School Curriculamentioning
confidence: 99%
See 3 more Smart Citations